Radiation-Induced Stable Radicals in Calcium Phosphates: Results of Multifrequency EPR, EDNMR, ESEEM, and ENDOR Studies - Fadis F. Murzakhanov; Peter O. Grishin; Margarita A. Goldberg; Boris V. Yavkin; Georgy V. Mamin; Sergei B. Orlinskii; Alexander Yu. Fedotov; Natalia V. Petrakova; Andris Antuzevics; Marat R. Gafurov; Vladimir S. Komlev (Applied Sciences, 2021)
This article presents the results of a study of radiation-induced defects in various synthetic calcium phosphate (CP) powder materials (hydroxyapatite—HA and octacalcium phosphate—OCP) by electron paramagnetic resonance (EPR) spectroscopy at the X, Q, and W-bands (9, 34, 95 GHz for the microwave frequencies, respectively). Currently, CP materials are widely used in orthopedics and dentistry owing to their high biocompatibility and physico-chemical similarity with human hard tissue. It is shown that in addition to the classical EPR techniques, other experimental approaches such as ELDOR-detected NMR (EDNMR), electron spin echo envelope modulation (ESEEM), and electron-nuclear double resonance (ENDOR) can be used to analyze the electron–nuclear interactions of CP powders. We demonstrated that the value and angular dependence of the quadrupole interaction for 14N nuclei of a nitrate radical can be determined by the EDNMR method at room temperature. The ESEEM technique has allowed for a rapid analysis of the nuclear environment and estimation of the structural positions of radiation-induced centers in various crystal matrices. ENDOR spectra can provide information about the distribution of the nitrate radicals in the OCP structure.